Land‐use effects on surface water quality in temperate lowland peatlands - Silverthorn, Teresa; Aberg, Dan; Baker, Francesca; Bell, Chris; Evans, Chris D.; Gurd, Caroline; Holman, Ian P.; Howell, Graham; McEwen, Angus; Morrison, Ross; Oakley, Josh; Southon, Francesca; et al. (Wiley, 2026)
Peatlands are important ecosystems for carbon storage, water regulation, water quality and other valuable ecosystem services that have been heavily impacted by drainage and conversion to grassland and cropland. Rewetting, or raising of the water table closer to the ground surface, is proposed as a solution to reduce peatland subsidence and carbon losses. Both peatland drainage and peatland rewetting may have unintended impacts on water quality, either by introducing solutes from the water used for rewetting, or by leaching of substances accumulated in peat. Here, we examined the effects of land use on UK lowland peat surface water chemistry by collecting a total of 350 surface water samples from 77 individual water bodies (ditches, streams, ponds) in 2024, across 33 sites representing the range of temperate lowland peatland types. Samples were measured for a wide array of chemical determinands including: carbon (C), nitrogen (N) and phosphorus (P), heavy metals, other anions and cations, and dissolved greenhouse gas concentrations. We found some clear patterns related to land use, notably high nitrate concentrations in surface waters draining croplands. Macronutrient stoichiometry revealed similar patterns at grassland, conservation‐managed and rewetted sites indicative of N and P co‐limitation, suggesting that rewetting leads to a nutrient balance comparable to natural conditions. Peatland type (bog vs. fen) was more important than land use in explaining patterns in most ion concentrations. Site and regional histories were more important than land use for patterns of heavy metal concentrations, indicating the importance of considering regional historical industrial activity. Overall, peatland land use can be an important driver of key nutrients and their stoichiometry, with no consistent negative impacts of peatland rewetting on water quality nor greenhouse gases.
Keywords: 3103 Ecology; 15 Life on Land; Ecology; 31 Biological sciences; 37 Earth sciences; 41 Environmental sciences; biogeochemistry; greenhouse gases; land use; lowland peatlands; macronutrients; nutrient stoichiometry; peatland drainage; peatland rewetting; water chemistry; Water Quality; Soil; Phosphorus; Agriculture; Carbon; Nitrogen; United Kingdom; Wetlands; Metals, Heavy